Hunting in Indonesian New Guinea: dogs, conservation and culture - Pattiselanno, Freddy; lloyd, Janice K F; Krockenberger, Andrew; Arobaya, Agustina Yohana Setyarini; Sheil, Douglas (Ethnobiology and Conservation, 2023)
Hunting has a complex and contested relationship with conservation: it can deplete and threaten vulnerable wildlife but can also motivate protection and good stewardship. This study aims to advance the ethnographic information of hunting with dogs, in particular, the increasing use of dogs in hunting, as such practice is a particular concern among conservationists. We present a case study from the lowland costal forest of Tambrauw in West Papua Province – Indonesian New Guinea using information gathered by assessing the activities and success of thirty-three hunters. The hunters identified 301 successful kills in a total of 654 hours of hunting. Five different prey species were reported across the study sites in a 7-month time period. Interestingly, active hunting without dogs had a higher yield (kills per hour) than hunting with them (0.700 versus 0.38 kills per hour), especially for deer, but hunting with dogs is the only method that seems to favour the capture of pigs over deer. Dogs are not valued for their role in hunting alone but also have less tangible cultural values also protect hunters and also their families from animals and spirits. We conclude that hunting with dogs is the only method that seems to favour the capture of pigs over deer. We find that dogs can provoke social conflicts and other problems. More attention should be given to local hunting and the methods used. Hunting with dogs impacts the quantity and composition of the hunt, this requires a careful appraisal, as dogs also provide wider cultural and protective roles.